Rotavirus genotypes in Malaysia and universal rotavirus vaccination - Lee, Way Seah; Lim, B.T.Y.; Chai, P.F.; Kirkwood, C.D.; Lee, J.K.F. (Taylor & Francis, 2012)
Group A rotavirus (RV-A) genotypes isolated in Malaysia was studied to estimate the eff ectiveness of a universal RV-A vaccination in Malaysia. A simple mathematical model was used, with input from a two-year, two-center, prospective study on hospitalization of RV-A gastroenteritis (RVGE) in young children, published data on RV-A hospitalizations and genotypes, mortality on childhood GE, and published genotype-specifi c effi cacy data on two RV-A vaccines. Assuming a 95% vaccine coverage, the overall projected eff ectiveness was 75.7% to 88.1% for Rotateq® and 78.7% to 90.6% for Rotarix® against RVGE-related hospitalizations. The projected annual reduction in RVGE-related deaths was 27 to 32 deaths (from 34 deaths) for Rotateq® and 28 to 32 deaths annually forRotarix®. A universal RV-A vaccine is efficacious in reducing RVGE-related hospitalizations and mortality in Malaysia.